Calcitonin gene-related peptide (CGRP) receptors are important to maintain cerebrovascular reactivity in chronic hypertension. - Zhenghui Wang; Belén Cantó Martorell; Thomas Wälchli; Olga Vogel; Jan Fischer; Walter Born; Johannes Vogel (PLoS ONE, 2015)
Cerebral blood flow autoregulation (CA) shifts to higher blood pressures in chronic hypertensive patients, which increases their risk for brain damage. Although cerebral vascular smooth muscle cells express the potent vasodilatatory peptides calcitonin gene-related peptide (CGRP) and adrenomedullin (AM) and their receptors (calcitonin receptor-like receptor (Calclr), receptor-modifying proteins (RAMP) 1 and 2), their contribution to CA during chronic hypertension is poorly understood. Here we report that chronic (10 weeks) hypertensive (one-kidney-one-clip-method) mice overexpressing the Calclr in smooth muscle cells (CLR-tg), which increases the natural sensitivity of the brain vasculature to CGRP and AM show significantly better blood pressure drop-induced cerebrovascular reactivity than wt controls. Compared to sham mice, this was paralleled by increased cerebral CGRP-binding sites (receptor autoradiography), significantly in CLR-tg but not wt mice. AM-binding sites remained unchanged. Whereas hypertension did not alter RAMP-1 expression (droplet digital (dd) PCR) in either mouse line, RAMP-2 expression dropped significantly in both mouse lines by about 65%. Moreover, in wt only Calclr expression was reduced by about 70% parallel to an increase of smooth muscle actin (Acta2) expression. Thus, chronic hypertension induces a stoichiometric shift between CGRP and AM receptors in favor of the CGRP receptor. However, the parallel reduction of Calclr expression observed in wt mice but not CLR-tg mice appears to be a key mechanism in chronic hypertension impairing cerebrovascular reactivity.